Biochar-based slow/controlled-release fertilizer for sustainable agriculture : Recent advances, challenges and future prospects. - Daniel Hong Heng, Sim; Ivy Ai Wei, Tan; Leonard Lik Pueh, Lim; Freddy Kuok San, Yeo; Surisa, Phornvillay; M., Abat; Su Shiung, Lam; B. H., Hameed (Elsevier, 2025)
The excessive and inappropriate use of conventional fertilizer with high solubility leads to low nutrient use efficiency and environmental pollution through leaching, volatilization and surface runoff. Thus, slow/ controlled-release fertilizer is urgently sought-after to mitigate environmental harm while alleviating crop production. Recently, biopolymer encapsulated biochar-based slow/controlled-release fertilizer has gained much interest due to its environmentally friendly nature and potential in supplying nutrients at a slower rate. This paper provided a comprehensive review of the nutrient loading capacity of various pristine biochar and modified biochar, and outlined three major fabrication processes (as nutrient carrier, additive and encapsulating material) of biochar-based slow/controlled-release fertilizer. This paper also evaluated the slow-release mechanism, effect of fertilizer on soil properties and plant growth as well as the recent advances on economic assessment. The formulation and modification methods of biopolymer were extensively discussed, and the effect of modification on the properties of biopolymer such as porosity, biodegradability, tensile strength, water resistibility and water solubility were also highlighted. An insight into the fertilization strategy including fertilizer coupled with placement method or pristine biochar was provided. This paper outlined the recent advances and future directions of biochar-based slow/controlled-release fertilizer for sustainable agriculture.